Purification of non-halal income in Malaysian Islamic banks: an overview = Penyucian pendapatan tidak-Halal di bank-bank Islam Malaysia: satu tinjauan - Mohd Yunus, Saidatolakma; Haneef, Sayed Sikandar Shah; Kamaruddin, Zuraidah; Mahmud, Mek Wok (IIUM Press, International Islamic University Malaysia, 2017)
Purification of non-halal income (NHI) is the process of deducting non-halal or tainted income deemed unacceptable by SharÊ‘ah from the total income generated in Islamic banks. It is undeniable that SharÊ‘ah non-compliance events still occur in Islamic banking system considering the fact that Islamic banks have not been able to fully comply with the requirements of SharÊ‘ah in their transactions, operations and financial activities. The realization of SharÊ‘ah non-compliance events in Islamic banks in some situations involve a financial impact which leads to NHI. All NHI identified must be purified since Islam does not allow any non-halal income to be held, kept and utilised for their own benefits. This paper will give a new insight on purification of NHI by first delineates the concept of mal haram in Islam as well as the SharÊ‘ah non-compliant events realized in the banks, with special reference to cases involving Islamic banks in Malaysia.